(untitled) (Research, Society and Development, 2022)
Harvesting mangoes at the wrong time of maturation impairs the final quality of the product, therefore, deciding the correct time for the shape of the same is an essential factor for the fruits to have better physical, chemical and nutritional properties. Therefore, due to the lack of information to help in the proper choice of harvest time for this variety, the objective was to analyze physicochemical characteristics of fruits in four stages of development, aiming to identify the ideal harvest point for ’Ubá’ mango. A completely randomized design was used, with nine replications for each stage. The skin and pulp color of ’Ubá’ mango were evaluated through L*, a* and b coordinates, soluble solids content, titratable total acidity, pH and ratio. Thus, the results of this study concluded that the ’Ubá’ mango can be harvested at the greenish stage, as it has a total soluble solids content of 12.05, a pH of 3.89 and a ratio of 89.63, values that are satisfactory according to the legislation. current, correlated with the yellowish color of the pulp, defined by the increase of the a* coordinate from 4.12 to 23.78 and the b* coordinate from 60.43 to 81.71, an important criterion for the commercialization of the fruit.